Efektivitas E-Kelurahan Air Tawar Barat dalam Pelayanan Publik Kota Padang - Hayati, Jovita; Rahayu, Mariyah Putri; Brezki, Serena Desy; Fani, Savira Tri; Helmi, Rahmadhona Fitri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research analyzes the effectiveness of e-Government through the e-Kelurahan program and its impact on public services in Padang City. With a descriptive qualitative approach, the research uses secondary data and interviews to understand the phenomenon in depth. This digital transformation is supported by the high number of internet users (63.61% of the total population of Padang City), which aims to improve efficiency, transparency and accessibility of public services. The results show an increase in the number of online document submissions as an indication of the program's success. However, challenges remain, including limited employee competence in information technology and lack of socialization to the public. Supporting tools are in place, but require regular updates to keep the system running smoothly. Padang City Government has strengthened application security to protect citizen data. The e-Kelurahan program has great potential to improve the quality of public services, although it needs to be balanced with staff training and effective socialization to the community.